COMPARATIVE FORMOF ADJECTIVES BY PREFIX UM- IN TOBA BATAK - Esron Ambarita (LPPM Universitas Darma Agung, 2019)
The objectives of this study are to investigate comparative form of adjectivesby prefix um- in Toba Batak. The results show that comparative form of adjectivesby prefix um- in Toba Batak result invarious morphological and phonological processesas follows: (1) if prefix [um-] is attached to adjectives preceded by vowels, the last phoneme of the prefix is doubled ([um-]→[umm-]). (2) if the initial phoneme is a bilabial plosive voiced consonant [b], prefix [um-] is pronounced [ub-] as its allomorph. (3) if the initial phoneme is a velarplosive voiced consonant [g], prefix [um-] →[uŋ-]. (4)ifthe initial phoneme is a palato alveolar affricate voiced consonant [j]prefix [um-]→[un-] in spellingbut [uj-] in pronunciation. (5) ifthe initial phoneme is a bilabial nasal voiced consonant [m] prefix [um-] does not change. (6) ifthe initial phoneme is analveolar nasal voiced consonant [n]prefix [um-]→[un-] both in spelling and in pronunciation. (7)ifthe initial phoneme isa bilabial plosive voiceless consonant [p],prefix [um-]→[um-]in spelling but pronounced [up-]. (8) if the initial phoneme is an alveolar rolled voiced consonant [r], prefix[um-]→ [ur-] both in spelling and in pronunciation. (9) ifthe initial phoneme is an alveolar fricative voiceless consonant [s], prefix[um-]→ [un-] in spelling but [us-] in pronunciation. (10)if the initial phoneme is an alveolar plosive voiceless consonant [t], prefix [um-]→ [un-] in spellingbut it is pronounced [ut-].